Hedonic price model on the effect of mass rapid transit (MRT) station development towards housing price - Ong, Zhi Hui (2023)
A good transportation system plays an important role in a country, city, housing and even people. Due to the importance of transportation, many researchers have carried out studies on the effects of railway development on house prices across the globe. Malaysia, as a developing country, currently has a lot of new infrastructure development and one of them is the railway station. However, there is still a lack of research related to the effects of railway stations on housing prices. Besides, the effects of railway stations on housing prices are still blurry, as researchers conducted globally show some negative and positive effects. Furthermore, a lack of information will affect the decision-making of authorities and related parties on urban planning or any new related investment. Therefore, this study focuses on the effect of MRT station development on housing prices. The study adopts a quantitative approach and utilizes the hedonic price model to explore the relationship between both. The secondary data used in this study is mainly from the Valuation Management System (VMS) and Google Maps. Physical attributes such as housing type, title interest, year of transaction, floor area, and distance to the MRT station are identified as the main factors affecting the housing price. Six condominiums were selected, of which three were within 500 meters of Pusat Bandar Damansara MRT station and the other three were outside of 500 meters. The analysis shows that there is a significant positive effect of housing prices within 500 meters of the MRT station. This study has implications for urban planners, government and private sector valuers, and investors in terms of establishing accurate valuation models and making informed investment decisions. This study contributes valuable knowledge on the effect of MRT station development towardshousing prices in Malaysia.